Associative Memory Extinction Is Accompanied by Decayed Plasticity at Motor Cortical Neurons and Persistent Plasticity at Sensory Cortical Neurons - Guo, Rui; Ge, Rongjing; Zhao, Shidi; Liu, Yulong; Zhao, Xin; Huang, Li; Guan, Sodong; Lu, Wei; Cui, Shan; Wang, Shirlene; Wang, Jin-Hui (Frontiers in Cellular Neuroscience, 2017)
Associative memory is essential for cognition, in which associative memory cells and their plasticity presumably play important roles. The mechanism underlying associative memory extinction versus maintenance remains unclear, which we have studied in a mouse model of cross-modal associative learning. Paired whisker and olfaction stimulations lead to a full establishment of odorant-induced whisker motion in training day ten, which almost disappears if paired stimulations are not given in a week, and then recovers after paired stimulation for an additional day. In mice that show associative memory, extinction and recovery, we have analyzed the dynamical plasticity of glutamatergic neurons in layers II~III of the barrel cortex and layers IV~V of the motor cortex. Compared with control mice, the rate of evoked spikes as well as the amplitude and frequency of excitatory postsynaptic currents increase, whereas the amplitude and frequency of inhibitory postsynaptic currents decrease at training day ten in associative memory mice. Without paired training for a week, these plastic changes are persistent in the barrel cortex and decayed in the motor cortex. If paired training is given for an additional day to reevoke associative memory, neuronal plasticity recovers in the motor cortex. Our study indicates persistent neuronal plasticity in the barrel cortex for cross-modal memory maintenance as well as the dynamical change of neuronal plasticity in the motor cortex for memory retrieval and extinction. In other words, the sensory cortices are essential for long-term memory while the behavior-related cortices with the inability of memory retrieval are correlated to memory extinction.